Transcriptomic analysis on pancreatic adenocarcinoma patients uncovers KRAS-mediated PPAR pathway alteration - Defazio, Giuseppe; Scolari, Federico; Fancelli, Sara; Polvani, Simone; Lavacchi, Daniele; Picariello, Lucia; Tubita, Alessandro; Luconi, Michaela; Antonuzzo, Lorenzo; Galli, Andrea; Pillozzi, Serena (Frontiers in Oncology, 2025)
The incidence and mortality of pancreatic adenocarcinoma (PC) are expected to increase in the coming years, with survival rates remaining poor due to limited treatment options. KRAS mutations, present in over 70% of PC cases, drive aggressive tumor behavior through metabolic reprogramming and immune evasion; however, clinically effective inhibitors for the most common mutations are still lacking. In this study, we analyzed RNA sequencing data from TCGA datasets, comparing tumor versus normal pancreatic tissues and stratifying samples based on KRAS mutation status. Our findings reveal significant dysregulation of the peroxisome proliferator-activated receptor (PPAR) signaling pathway in PC, particularly in the context of KRAS mutations. These findings were validated through RT-qPCR in an independent cohort of primary samples. Key genes, including CD36, FABP4, PLIN1, PLIN4, SCD5, and ACSLs, were consistently downregulated in tumor tissues, with further reductions observed in KRAS-mutated samples. Overall, this study highlights the critical role of PPAR pathway disruption in KRAS-mutated PC, which should be further addressed to improve current treatment strategies.